Evaluations of Antibacterial Properties of Zingiber purpureum Essential Oil Against 13 Different Gram-positive and Gram-negative Bacteria - Nataniel Tandirogang; Silvia Anitasari; Enos Tangke Arung; Swandari Paramita; Yung Kang Shen (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Indonesia's tropical forest is home to around 80% of the world's medicinal plants. One of these is Zingiber purpureum, which have traditionally been used to treat joint discomfort, the common cold, and jaundice. The rhizomes of this plant have been suggested to possess antibacterial action in the treatment of infections. In this study, Z. purpureum was screened for antibacterial activity against 13 bacteria (Gram-positive and Gram-negative).METHODS: Z. purpureum rhizomes were obtained and the distillated extracts were made to generate essential oil. The minimum inhibitory concentration (MIC) and Kirby Bauer disk diffusion methods were used to determine the antibacterial activity.RESULTS: All bacteria activity were inhibited by the essential oil of Z. purpureum at concentrations ranging from 2.5 vol% to 10 vol%. However, several bacterias (Escherichia coli, Pseudomonas aeruginosa, and Enterobacter cloacae) were inhibited at the lowest concentration (0.63 vol %), with the inhibition zones ranging from 6.7 mm to 8.0 mm. Meanwhile, the widest inhibition zone (13.3 mm) was reported on E. cloacae at 10 vol% concentration.CONCLUSION: A 10 vol% Z. purpureum rhizome extract inhibits Gram-positive and Gram-negative bacteria, particularly those that are resistant to a variety of antibiotics.KEYWORDS: Zingiber purpureum, antibacterial agents, susceptibility test, infection